2021
DOI: 10.1021/acs.est.1c05602
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Isotope Fractionation during the Exchange of Hg(0) between the Atmosphere and Land Surfaces: Implications for Hg(0) Exchange Processes and Controls

Abstract: Atmosphere–surface exchange of elemental mercury (Hg(0)) is a vital component in global Hg cycling; however, Hg isotope fractionation remains largely unknown. Here, we report Hg isotope fractionation during air–surface exchange from terrestrial surfaces at sites of background (two) and urban (two) character and at five sites contaminated by Hg mining. Atmospheric Hg(0) deposition to soils followed kinetic isotope fractionation with a mass-dependent (MDF) enrichment factor of −4.32‰, and negligible mass-indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(51 citation statements)
references
References 71 publications
6
45
0
Order By: Relevance
“…Light-driven Hg II reduction in systems with DOC is several orders of magnitude faster than dark reduction in the presence of DOC 30,68 . Our suggestion of photoreduction of rainwater Hg II is in line with isotopic data from agricultural soils 69 , in which O/N functional groups were suggested to be involved in the initial complexation of Hg II after deposition. As a consequence of the weaker Hg-O/N bond, rates of Hg II reduction are greater than when Hg II forms complexes with the chemically much stronger bonding thiol functional groups 64,68 .…”
Section: Origin and Fate Of Dissolved Gaseous Mercury (Dgm)supporting
confidence: 88%
See 1 more Smart Citation
“…Light-driven Hg II reduction in systems with DOC is several orders of magnitude faster than dark reduction in the presence of DOC 30,68 . Our suggestion of photoreduction of rainwater Hg II is in line with isotopic data from agricultural soils 69 , in which O/N functional groups were suggested to be involved in the initial complexation of Hg II after deposition. As a consequence of the weaker Hg-O/N bond, rates of Hg II reduction are greater than when Hg II forms complexes with the chemically much stronger bonding thiol functional groups 64,68 .…”
Section: Origin and Fate Of Dissolved Gaseous Mercury (Dgm)supporting
confidence: 88%
“…The dominance of net plant uptake of atmospheric Hg 0 over net rainfall Hg II deposition to the vegetated surface of peatlands might be partially due to Hg II in precipitation being more easily available for photoreduction and subsequent evasion back to the atmosphere than the Hg II associated with plant tissues. The relative importance of photoreduction of Hg II in rainfall can be explained by the abundance of organic R-O/N functional groups at peat and vegetation surfaces providing a weaker bond to Hg II to compete with the reduction process, during the time window required for Hg II to re-arrange to stronger bonding RS functional groups 30,64,69 . Once bound to the stronger RS functional groups, Hg II is less susceptible to reduction.…”
Section: Conclusion and Environmental Implicationsmentioning
confidence: 99%
“…We suggest that Hg in recent sediments of near-field lakes was primarily derived from tailing fugitive dust, which is expected to have comparable Hg isotope compositions as fed ores (i.e., no significant Hg isotope fractionation during mechanical separation). , We attribute the negative shifts in δ 202 Hg values in recent sediments from the middle- and far-field lakes to increasing contributions from the re-emission of legacy Hg from tailing deposits and contaminated soils. Re-emission of Hg involves reduction and volatilization processes, which are expected to enrich light Hg isotopes in the emitted gaseous elemental Hg(0). , …”
Section: Resultsmentioning
confidence: 99%
“…Re-emission of Hg involves reduction and volatilization processes, which are expected to enrich light Hg isotopes in the emitted gaseous elemental Hg(0). [28][29][30]46 Uptake of atmospheric Hg(0) by vegetation further enriches light Hg isotopes in vegetation, which are then transferred to soils. 47−50 The soils and vegetation in lake catchments have been reported to mainly exhibit a significant enrichment of light Hg isotopes.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al, 2016). Isotopic compositions of GEM net emissions from terrestrial surfaces were recently investigated, which showed lower δ 202 Hg (median: −1.13‰, IQR: −2.00-−0.47‰) and Δ 199 Hg (median: −0.13‰, IQR: −0.26-−0.02‰), and similar Δ 200 Hg (median: 0.02‰, IQR: −0.01-0.03‰) as compared with those of anthropogenic emissions (Figure 5; Table S3 in Supporting Information S1) (Yuan et al, 2019(Yuan et al, , 2021Zhu et al, 2022). Thus, decreasing surface emissions could also lead to decreases in GEM concentrations and Δ 200 Hg and increases in δ 202 Hg values, but would cause insignificant Δ 199 Hg shift because the GEM Δ 199 Hg at MCB and MAL in earlier years were close to that emitted from land surfaces.…”
Section: Causes Of the Changes In Gem Concentrations And Isotope Comp...mentioning
confidence: 88%